NORMATIVE ETHICS IN MANAGEMENT AND EDUCATION - Dedy Yusuf Aditya; Muh. Aripin Nurmantoro (Cakrawala Pedagogik, 2023)
This article is a literature review that discusses normative ethics in management and education, the purpose of writing this article is to discuss how normative ethics exist and develop in society, especially in the educational community related to students, teachers and all teaching staff and education, reveals various problems of violations of normative ethics that often occur in the world of education and how to instill good ethics in students as one of the goals of educational management. The research method used in this article is literature study or literature study from various sources such as books, journals, and also news about ethical issues in education. In the discussion of this article, it discusses the types of ethics that develop in society, namely descriptive ethics, normative ethics and meta-ethics, how ethics are used in management which become ethical principles, namely the principle of autonomy, the principle of honesty, the principle of justice, the principle of mutual benefit and principles of moral integrity and case studies on ethical violations in education.